Identifikasi Waste Pada Proses Produksi Untuk Meminimumkan Penggunaan Ruangan Menggunakan Pendekatan Lean Manufacturing - Nurwahidah, Andi; Achmad, Andi Muhammad Fiqri; Madi, Reskika Putri (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2025)
Kedai Kue ABC is a Small and Medium Enterprise (SME) that produces snacks such as cookies, bread, and sponge cakes. Its main product is white bread, which is supplied to five coffee shop outlets. Currently, the demand for white bread reaches 180 loaves per day from three outlets, but the SME can only fulfill 120 loaves, equivalent to supplying two outlets. This study aims to identify waste in the white bread production process and its root causes by applying lean manufacturing principles using the Value Stream Mapping (VSM) and Process Activity Mapping (PAM) methods. The process begins with mapping the current state, followed by analyzing the causes of waste using a fishbone diagram. Subsequently, a more efficient future state map is developed. The results identify two main types of waste: motion waste and transportation waste. The proposed improvements can reduce production time by up to 1,112 seconds (18.95 minutes). Recommendations include eliminating non-value-added activities, combining processes, increasing machine capacity, adding tool racks, rearranging the production layout, and applying the 5S principle to enhance production efficiency at Kedai Kue ABC